Brand Image Memediasi Celebrity Endorse dan Sosial Media Marketing terhadap Keputusan Pembelian Produk UMKM: Pisang Goreng Ny Ani – Malang - Rina Irawati; Meirina Nursahira; Setiyawan Setiyawan (Universitas Nusantara PGRI Kediri, 2025)
Digital marketing have a very important role in marketing a business, especially for MSME businesses. Social media offers great opportunities for MSMEs to grow and develop amidst fierce competition. Pisang Goreng Ny Ani is a micro-scale food business, which is currently a popular snack in Malang which was established in 2024. The purpose of the study was to determine the direct and indirect influence of Celebrity Endorsement and Social Media Marketing on purchasing decisions for MSME products through Brand Image. The research sample was 100 consumers of Pisang Goreng Ny Ani using the Hair et al formula and the Accidental Sampling technique. Data were obtained through questionnaires, then analyzed using descriptive statistics, multiple regression and path analysis. The results showed that celebrity endorsement and social media marketing had a strong influence on purchasing decisions where the significance was 0.009 and 0.015 respectively. Celebrity endorsement and social media marketing have an influence on brand image with a significance of 0.000 and 0.003. Brand image mediates the variables celebrity endorsement and social media marketing on purchasing decisions. The largest indirect influence is brand image mediating social media marketing on purchasing decisions with the largest beta value, namely 0.194